Pemenuhan Kesehatan Gigi Anak Penyandang Retardasi Mental Dalam Perspektif Hak Asasi Manusia - Nendika Dyah Ayu M.; Y. Trihoni Nalesti Dewi; Edi Sumarwanto (SOEPRA, 2018)
Mental retardation is a decrease in cognitive, motoric and social abilities.Mental retardation in indonesia reach 30.460 in 2012. Mental retardation characterized byindex IQ less than 70, it cause limitation in motoric skills such as brushing teeth.Theinability to brush their teeth will affect in their oral health, that can increase variousoral disease, so children with mental retardation need a affirmative action. Law Number36 Year 2009 on Health, Law of the Republic of Indonesia Number 8 Year 2016 on Personswith Disabilities and Law of the Republic of Indonesia Number 19 Year 2011 on RatificationConvention On The Rights Of Persons With Disabilities explained that children withmental retardation deserve highest degree of health without discrimination and getaffirmative action according to their disability.A method of the research is a qualitative method.The approach method is juridicalsociological. Data that used in this research are primary and secondary data.The primarydata are from interviews with pediatric dentist, director of the hospital , teachers SLB ,principal SLB and jurist. Secondary data are from literature study which supporting theprimary data.The results show that the existing regulation only give an obligation for the governmentto fullfil. If they are not implementing the regulation, there is no reporting mechanismand regulatory sanctions. In practice, the right to obtain socialization or informationabout dental health of children with mental retardation, the right to access facilities andparamedics without discrimination, and the right to get affirmative action such as dentalteam service, communication, visitation hours, dental chair and treatment specificallystated on the regulation of the minister of health number 89 of 2015 on dental and oralhealth efforts is not based on that regulation. Without any sanctions, the existingregulation has not been able to guarantee the compliance the right of dental health forchildren with mental retardation. So that it isn’t sufficient as a basic for the complianceof the human rights.